Trust and childhood maltreatment: evidence of bias in appraisal of unfamiliar faces. (9th September 2021) - Neil, Louise; Viding, Essi; Armbruster‐Genc, Diana; Lisi, Matteo; Mareschal, Isabelle; Rankin, Georgia; Sharp, Molly; Phillips, Harriet; Rapley, Jessica; Martin, Peter; McCrory, Eamon
Abstract : Background: Child maltreatment is associated with poorer social functioning and increased risk of mental health problems in adolescence and adulthood, but the processes underlying these associations remain unclear. Although crucial for establishing and maintaining relationships, trust judgements have not been experimentally investigated in children who have experienced abuse and neglect. Methods: A community‐based sample of 75 children aged 8–16 years with maltreatment documented on the basis of social services records, and a group of 70 peers matched on age, gender, cognitive ability, socioeconomic status, and ethnicity took part in the study. Children completed a trustworthiness face‐judgement task in which they appraised the trustworthiness of unfamiliar facial stimuli varying along a computationally modelled trustworthiness dimension. Results: In line with clinical observations that childhood maltreatment is associated with an atypical pattern of trust processing, children with maltreatment experience were significantly less likely than their peers to rate unfamiliar faces as trustworthy. Moreover, they were more variable in their trust attributions than their peers. Conclusions: The study provides compelling experimental evidence that children with documented maltreatment perceive others as less trustworthy than their peers and are less consistent in their estimates of trustworthiness in others. Over time, alterations in trust processing may disrupt the development of social bonds and contribute to 'social thinning' (a reduction in the extent and quality of social relationships), leaving children more vulnerable to environmental stressors, increasing risk of mental health difficulties.